A new species of Tarphius Erichson, 1845 (Coleoptera: Zopheridae) from North Africa and notes on an Iberian species - Serrano, Artur R.m.; Amorim, Isabel R.; Borges, Paulo A.v. (Zootaxa, 2013)
A new species of Tarphius Erichson, 1845 (Coleoptera: Zopheridae, Solier, 1834) is described from Morocco. Tarphius isabelae n. sp. is the fifth Tarphius species recorded in North Africa. In addition, we present some information on the Ibe-rian species, Tarphius kiesenwetteri Heyden, 1870.